Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
The zeros for the function
[tex]x=6,\:x=4i,\:x=-4i[/tex]
Step-by-step explanation:
Given the expression
[tex]y=x^3-6x^2+16x-96[/tex]
Plug in y = 0 to determine all the zeros
[tex]x^3-6x^2+16x-96=0[/tex]
as
[tex]x^3-6x^2+16x-96=\left(x-6\right)\left(x^2+16\right)[/tex]
so the expression becomes
[tex]\left(x-6\right)\left(x^2+16\right)=0[/tex]
Using the zero factor principle
if ab=0, then a=0 or b=0 (or both a=0 and b=0)
[tex]x-6=0\quad \mathrm{or}\quad \:x^2+16=0[/tex]
solving
[tex]x-6=0[/tex]
[tex]x = 6[/tex]
solving
[tex]x^2+16=0[/tex]
subtract 16 from both sides
[tex]x^2+16-16=0-16[/tex]
[tex]x^2=-16[/tex]
[tex]\mathrm{For\:}x^2=f\left(a\right)\mathrm{\:the\:solutions\:are\:}x=\sqrt{f\left(a\right)},\:\:-\sqrt{f\left(a\right)}[/tex]
[tex]x=\sqrt{-16},\:x=-\sqrt{-16}[/tex]
as
[tex]x=\sqrt{-16}[/tex]
[tex]\sqrt{-16}=\sqrt{-1}\sqrt{16}[/tex]
as
[tex]\sqrt{-1}=i[/tex]
so
[tex]x=4i[/tex]
and
[tex]x=-\sqrt{-16}[/tex]
[tex]-\sqrt{-16}=-\sqrt{-1}\sqrt{16}[/tex]
as
[tex]\sqrt{-1}=i[/tex]
so
[tex]x=-4i[/tex]
Thus, the zeros for the function
[tex]x=6,\:x=4i,\:x=-4i[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.